Sequential occurrence of diffuse large B-cell lymphoma and carcinoma in the nasopharynx: A case report. Issue 2 (January 2018) - Hong, Yong Tae; Hong, Ki Hwan
Abstract: Background: The sequential occurrence of the 2 malignancies development of nasopharyngeal carcinoma (NPC) and lymphoma is extremely rare and their coexistence raises the question of a common etiologic factor. Clinical findings/clinical concerns: A 71-year-old previously healthy man presented with diffuse large B-cell lymphoma (BCL) followed by NPC almost 2 years later with Epstein–Barr virus (EBV) positive. Diagnosis: Endoscopic examination characterized a fixed, hard and nontender mass in the nasopharynx and biopsies were done. Intervention: A patient successfully underwent chemotherapy for lymphoma and chemoradiation for carcinoma sequentially. Outcomes: He was followed up every 3 months for 1 year with endoscopic and radiological examinations. The nasopharynx mass was completely resolved after chemoradiation therapy. Conclusion: The presentation with diffuse large B-cell lymphoma (BCL) and NPC in this patient was perhaps caused by dual EBV infection or a different oncogenic mechanism.